Electronic document and records management systems - McLeod, Julie (Records management journal ;, 2005)
The final issue of the year always has a theme, and it is no coincidence that in 2005 thetheme is electronic document and records management systems (EDRMS). When theEditorial Advisory Board considered potential themes at its annual meeting last year itfelt it would be particularly appropriate to explore whether or not EDRMS haddelivered what they promised and/or what had been hoped for, given the flurry ofactivity on EDRMS procurement and implementation in the lead up to freedom ofinformation legislation in the UK. Although we did not intend to focus exclusively onthe UK, all of the contribut.